2005
DOI: 10.1099/ijs.0.63551-0
|View full text |Cite
|
Sign up to set email alerts
|

Phyllobacterium trifolii sp. nov., nodulating Trifolium and Lupinus in Spanish soils

Abstract: Bacterial strain PETP02 T was isolated from nodules of Trifolium pratense growing in a Spanish soil. Phylogenetic analysis of the 16S rRNA gene sequence showed that this strain represents a member of the genus Phyllobacterium. However, divergence found with the 16S rRNA gene sequence of the single recognized species of this genus, Phyllobacterium myrsinacearum, indicated that strain PETP02 T belongs to a different species. The results of DNA-DNA hybridization, phenotypic tests and fatty acid analyses confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
74
1
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 141 publications
(81 citation statements)
references
References 22 publications
2
74
1
4
Order By: Relevance
“…Plants house several endophytes within their tissues and multiple studies have reported the presence of endophytes in legumes (Muresu et al, 2008;Ibañez et al, 2009;Muresu et al, 2010). One of the genera in our study, Phyllobacterium (Table 1) is a known nodule endosymbiont and is capable of fixing nitrogen (Valverde et al, 2005;Baimiev et al, 2007). However, in our study no symbiosis or nitrogen fixation related genes were detected for the isolates of this genus.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Plants house several endophytes within their tissues and multiple studies have reported the presence of endophytes in legumes (Muresu et al, 2008;Ibañez et al, 2009;Muresu et al, 2010). One of the genera in our study, Phyllobacterium (Table 1) is a known nodule endosymbiont and is capable of fixing nitrogen (Valverde et al, 2005;Baimiev et al, 2007). However, in our study no symbiosis or nitrogen fixation related genes were detected for the isolates of this genus.…”
Section: Discussionmentioning
confidence: 46%
“…However, this needs to be confirmed using authentication experiments (Howieson et al, 1995). Previous studies indicate that endophytes can have three main functions inside root nodules, firstly as true rhizobial endosymbionts capable of inducing nodulation and performing nitrogen fixation (Valverde et al, 2005;Ardley et al, 2012). Secondly, as helper bacteria increasing plant health and/or yield when co-inoculated with rhizobia (Annapurna et al, 2013;Tariq et al, 2014), and finally, as opportunistic endophytes thriving in this nitrogen riche nodule environment (Dudeja et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The genus includes P. myrsinacearum and two recently described species, Phyllobacterium trifolii (Valverde et al, 2005) and Phyllobacterium catacumbae (Jurado et al, 2005).…”
mentioning
confidence: 99%
“…Lane M is a DGGE marker 1447 tested). One of these strains had been identified as Phyllobacterium trifolii (Valverde et al 2005, GenBank accession number AY786080); the other one is an uncultured Phyllobacterium strain (Barbieri et al 2005, GenBank Accession Number AY599681). Attempts were made to isolate these by streaking on a selective medium, i.e.…”
mentioning
confidence: 99%